Investigation on The Factors Affecting Lifestyle of Professionals in The Construction Industries (Kerala and Tamil Nadu) - K S, Anandh; K, Gunasekaran; M A, Mannan (International Journal of Integrated Engineering, 2020)
One of the vital assets of any industry is human resources. In general, the majority of works are carried out by humans in the construction industries. Study on the assessment of quality of civil engineering construction professionalsâ€™ lifestyle is very limited and hence the motto of this study is to understand the lifestyle of construction professionals and to assess the various factors affecting the lifestyle of them. To analyze the effects of societal behavior and to develop a model to study the impact of various factors in a construction professionalâ€™s lifestyle; a mixed approach had been adopted in this study. The instrument used in the study was a questionnaire survey conducted from 180 construction professionals working in different firms in Kerala and Tamil Nadu states of India and these were analyzed using structural equation modeling techniques. Factors affecting the construction professionalâ€™s lifestyle are: financial factors, organizational factors, quality, health and environmental factors, work-related factors, and social factors. Hence by foreseeing the factors and adopting favorable changes in a construction professionalâ€™s life, they may attain a better lifestyle. This study recommends the strategy to be considered for the improvements of lifestyle of the construction professional especially for â€œCivil Engineersâ€.